What Are Reviewers Looking For? A Qualitative Analysis of Open-Ended Responses from a Questionnaire Sent to Faculty in Agricultural Communications - Quisto Settle; Lauri M Baker; Alyssa Rockers (Journal of Applied Communications, 2020)
While peer review is the best system available for assessing the quality of research manuscripts, the system is imperfect at best. How peer review is conducted is often guided by unwritten rules, which can make writing articles for peer review more difficult. New reviewers also lack information on what other reviewers are looking for. This project assessed what reviewers were looking for when evaluating research papers. An anonymous link was sent to agricultural communications faculty members were eligible to review papers. There were 22 responses from the 43 faculty members who were sent the link to participate. Processes for reviewing varied, but it was typical to take notes while reading the article. About half of reviewers spent less than two hours per article. Overarching criteria reviewers were looking for were connection between sections of the paper, overall quality of work, writing quality, clarity, and the contribution of the work. Each section of research papers was also addressed in the study. The results of this study provide an overall roadmap for what agricultural communications reviewers are looking for, but it needs to be noted that different reviewers were looking for different things, so there will likely never be a single right approach for authors trying to clear the peer review hurdle. Future research is needed to further clarify the peer review process, including authors and those who have overseen the peer review process, such as editors and conference organizers.
Keywords: peer review; manuscript preparation; journal publications